A review on combined solar-membrane systems for wastewater treatment in Africa - Nouhou Moussa, Abdoul Wahab; Zrelli, Adel; Sawadogo, Boukary; Chemini, Rachida (Frontiers in Membrane Science and Technology, 2025)
Africa’s growing water stress and energy access challenges necessitate sustainable wastewater treatment solutions. This review critically examines three emerging approaches: solar-based, membrane-based, and hybrid solar-membrane systems, across the African continent. Solar technologies, including solar water disinfection, photocatalysis, and advanced oxidation processes, demonstrate significant potential in sun-rich regions, achieving more than 90% pathogen and contaminant removal in decentralized settings. Membrane bioreactors (MBRs) and advanced filtration systems show robust performance in industrial applications, with 95%–99% pollutant rejection, though their energy demands remain a significant constraint. Hybrid solar-membrane systems synergize these advantages, as evidenced by case studies in Kenya (solar-MBR for aquaculture, 40% energy autonomy) and Namibia (solar-powered desalination, 99.7% salt rejection). Despite technological promise, adoption barriers persist, including high capital costs, technical capacity gaps, and policy fragmentation. This review analyze 32 implementations across 17 African countries, evaluating performance metrics, scalability, and socioeconomic viability. Key findings highlight the cost-effectiveness and sustainability gains from waste-derived membranes (e.g., geopolymers, recycled plastics, oasis waste), nanoparticle-enhanced photocatalysts (TiO2/MnO2), and modular system designs tailored to off-grid and resource-limited settings. The review concludes with policy recommendations to accelerate deployment. These include fostering decentralized systems in peri-urban and rural areas, promoting public-private partnerships to finance infrastructure, and supporting localized research to adapt technologies to diverse hydroclimatic and socio-economic conditions. Together, these approaches offer a viable pathway toward achieving SDG 6 and SDG 7 in Africa.